Rilevanza pubblica delle comunità religiose nella dimensione giuridica europea (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La presenza religiosa nella sfera pubblica - 2. La libertà religiosa collettiva nella CEDU - 3. La condizione giuridica delle confessioni religiose nel diritto della UE - 4. Identità confessionali e identità nazionali europee - 5. Il ruolo “pubblico” delle istituzioni religiose negli Stati europei - 6. In particolare: a) la rilevanza costituzionale dei soggetti confessionali in Germania - 7. Segue: b) la condizione giuridica delle confessioni religiose in Italia.Public relevance of religious communities in the European legal dimensionThe religious phenomenon appears relevant both on an individual level and on a social level. In many cases religious experience, on the one hand, helps to draw the personal identity of the subject; on the other, it is an element that characterizes various aspects of civil society, up to the influence of the political and institutional dynamics of many contemporary state systems. This paper intends to demonstrate that the religious phenomenon does not appear confined only in the strictly private sphere, but lives and manifests itself also in the public dimension. This approach seems to be confirmed, among other things, by the new public role that religious communities are progressively taking on in the European legal sphere, as well as within individual state systems in Europe. From the analysis of the rules in force both at the European and national level, this work therefore derives a significant legal recognition of the public relevance of religions and religious communities that are direct institutional expression, paying particular attention to the experience gained in the German law and in the Italian legal system.